Education in Sierra Leone : Present Challenges, Future Opportunities - World Bank (Washington, DC: World Bank, 2012)
The purpose of this report is to provide an analysis of the education sector that enables a shared understanding among stakeholders, and thus lays a foundation for the preparation of an Education Sector Plan. With this objective in mind, the study outlines the current status of the education sector and highlights issues that policy makers need to address to move the sector forward. It also simulates a few policy scenarios and their financial implications to facilitate discussions about future feasible, affordable, and sustainable policy options. The coverage of this report -- a stock-taking exercise based on data, studies, reports, and documents available up to the 2004/05 school year -- is limited to key factors, including access, quality, equity, management, and finance, and has an emphasis on basic education.